Measurement of the exclusive γγ → μ+μ− process in proton–proton collisions at √s = 13 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2018)
The production of exclusive γγ → μ+μ− events in proton–proton collisions at a centre-of-mass energy of 13 TeV is measured with the ATLAS detector at the LHC, using data corresponding to an integrated luminosity of 3.2 fb−1. The measurement is performed for a dimuon invariant mass of 12 GeV < mμ+μ− < 70 GeV. The integrated cross-section is determined within a fiducial acceptance region of the ATLAS detector and differential cross-sections are measured as a function of the dimuon invariant mass. The results are compared to theoretical predictions both with and without corrections for absorptive effects.